DCE‐MRI for early evaluation of therapeutic response in esophageal cancer after concurrent chemoradiotherapy and its values in predicting HIF‐1α expression. Issue 3 (7th September 2021) - Xie, Xiaodong; Gu, Lingling; Guo, Zhen; Tao, Hua; Zhou, Yiqin; Shen, Wenrong; Zhou, Zhengyang
Abstract: To examine the feasibility of quantitative dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) in the early assessment of the therapeutic response to concurrent chemoradiotherapy (CRT) in esophageal cancer (EC) patients and to determine its value in predicting HIF‐1α expression. EC patients underwent DCE‐MRI 1 week pre‐CRT and 3 weeks post‐CRT (3w‐CRT). According to tumor regression post‐treatment, patients were divided into sensitive group (SG) and resistant group (RG). HIF‐1α expression was assessed by immunohistochemistry (IHC). Quantitative parameters (ktrans, kep, and ve) were compared between the SG and RG groups, as well as between the HIF‐1α(+) and HIF‐1α(−) groups. Receiver operating characteristic (ROC) curve analysis was performed to detect the best predictor of the above parameters in the therapeutic response and in predicting HIF‐1α expression. Totally 34 and 5 patients were included in the SG and RG, respectively. Pre‐ktrans and pre‐kep were decreased significantly in the SG at 3w‐CRT ( p  < .01), whereas only pre‐kep was decreased in the RG ( p  = .037). Pre‐ktrans was higher in the SG compared with the RG ( p  < .01). Meanwhile, absolute Δktrans (post‐ktrans– pre‐ktrans) was reduced more substantially in the SG compared with the RG. Δktrans also had the highest area under the curve (AUC = 0.929) in distinguishing SG from RG. Based on IHC, 13 and 11 patients were HIF‐1α(+) and HIF‐1α(−), respectively. At 3w‐CRT, post‐ktrans was markedly lower than pre‐ktrans in the HIF‐1α(+) group ( p  < .01); however, both ktrans and kep in the HIF‐1α(−) group were dramatically reduced than pre‐treatment values (both p  < .01). Pre‐ktrans was significantly higher in the HIF‐1α(−) group compared with the HIF‐1α(+) group ( p  = .002) and constituted an excellent parameter for predicting HIF‐1α expression (AUC = 0.881). DCE‐MRI is effective in the early assessment of the therapeutic response after CRT, offering a novel noninvasive method for predicting HIF‐1α expression in advanced EC patients. Abstract : To examine the feasibility of quantitative DCE‐MRI in the early assessment of the therapeutic response to concurrent chemoradiotherapy in esophageal cancer patients and to determine its value in predicting HIF‐1α expression.